Role of Color Doppler Ultrasonography in Evaluation of Scrotal Swellings: Pattern of Disease in 120 Patients With Review of Literature - Rizvi, Syed Amjad Ali; Ahmad, Ibne; Siddiqui, Mohammed Azfar; Zaheer, Samreen; Ahmad, Kaleem (Urology Journal, 2011)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Purpose: To determine the value of color Doppler ultrasonography (CDUS) as a routine investigational method for diagnosis of scrotal pathologies. Materials and Methods: This prospective observational study (case series) was carried out over a period of 16 months on 122 patients in the age range of 13 to 70 years old, who presented with scrotal swellings. After adequate history taking and examination, CDUS was performed. The diagnosis of the surgeon and that of radiologist were compared with final outcome, which was based on course and outcome of the disease, fine needle aspiration cytology results, and operative findings. Results: The final diagnoses were epididymitis or epididymo-orchitis (46), hydrocele (26), varicocele (16), testicular malignancy (16), orchitis (6), testicular torsion (4), spermatic cord injury (2), hematocele (2), and pyocele (2). Color Doppler ultrasonography accurately diagnosed all cases of epididymitis or epididymo-orchitis, spermatic cord injury, testicular torsion, varicocele, and hydrocele (sensitivity 100% and specificity 100%). Of 16 subjects diagnosed as testicular malignancy on CDUS, only 14 were subsequently found to have malignancy. Two cases of orchitis were wrongly diagnosed as malignancy. Similarly, of 6 patients diagnosed as orchitis, 1 was found to have seminoma (sensitivity 87.5% and specificity 66.7%). Overall sensitivity of CDUS in diagnosing scrotal diseases was 98% while specificity was 66.7%. Conclusion: Color Doppler ultrasonography is an excellent, a safe, and reliable method for evaluating patients with scrotal diseases. It aids in diagnosis of testicular tumors and reduces the number of unnecessary exploratory operations. It is especially important in conditions like testicular torsion where immediate diagnosis is required.